Dynamic Risk Stratification for Recurrence in Medullary Thyroid Cancer. (23rd August 2013) - Ho, Allen S.; Palmer, Frank L.; Shah, Jatin P.; Tuttle, R. Michael; Ganly, Ian
Abstract : Objectives: Develop a dynamic postoperative risk stratification tool for medullary thyroid cancer (MTC) recurrence, based on patient, tumor and treatment characteristics. Methods: 124 MTC patients who were treated entirely at Memorial Sloan‐Kettering Cancer Center between 1986‐2010 were identified. Immediate postoperative risk groups were defined as low, intermediate, and high based upon extent of extrathyroid extension, presence of regional or distant metastases and preoperative calcitonin level. Response to therapy categories were then defined as excellent, acceptable, and poor based upon 6‐month calcitonin level and presence of radiological structural disease. Overall risk groups based upon the immediate postoperative risk and the response to therapy category were then defined. Results: The median age was 55 years (range: 6‐88). Median follow‐up was 66 months (range: 1‐229). In the immediate postoperative risk groups, the 5‐year risk of structural recurrence for low, intermediate, and high risk groups was 5.9%, 24.9%, and 67.8% respectively ( P < 0.001). For the overall risk groups, the 5‐year risk of structural recurrence for low, intermediate, and high risk groups was 3.2%, 24.0%, and 45.9% ( P < 0.001). Low risk patients with poor responses increased their recurrence risk from 5.9% to 24.9%, while high risk patients with excellent responses reduced their recurrence risk from 67.8% to 24.9%. Conclusions: A clinically useful dynamic risk stratification tool to predict risk of recurrence in MTC patients over time is introduced. Its prognostic value may augment patient counseling on prognosis and help determine the frequency and extent of follow up investigations.